Micropropagation of withania somnifera through forced axillary branching and synthetic seed production from vegetative propagules - Kaur, Manveer (My University, 2013)
The present investigation was carried out on an important medicinal plant Withania somnifera belonging to family solanaceae. The plant is commonly known as Ashwagandha or winter cherry and is documented in Ayurveda and indigenous medical system for the treatment of a variety of diseases and disorders. The nodal segments and shoot tips were excised from an elite field grown mature plant and thereafter planted on variously supplemented Murashige and Skoog’s medium for the induction of multiple shoots. Shoot apices were encapsulated with sodium alginate to produce artificial seeds and their germination potential was evaluated after different periods of storage at 4oC. Withania somnifera exhibited good degree of multiple shoot proliferation from nodal explants and shoot tips. Multiple shoot proliferation from nodal segments was achieved on MS medium supplemented with BAP( 4.4-6.6 µM) either alone or in combination with KN(4.65µM) or IAA(8.5µM) or TDZ(0.5µM) where 8-10 shoots were obtained after 8 weeks of culturing. Best results were, however, obtained on MS+ BAP(6.6µM) + IAA(8.5µM) where 12-15 shoots were formed per node after 8-10 weeks of culturing. Shoot apices also exhibited multiple shoot proliferation when cultured on MS medium supplemented with BAP (6.6µM-8.8µM) either alone or in supplement with IAA (8.5µM) or KN (9.3 µM) or with NAA (2.6µM) . BAP alone was less effective in inducing multiple shoots while in combination with IAA or Kinetin significantly enhanced multiple shoot proliferation. Best medium for multiple shoot proliferation from shoot tip was BAP(6.6µM) +IAA(8.5µM) where a maximum of 20-25 shoots were regenerated after 10 weeks of culturing followed by BAP(8.8)+ KN(9.3µM) where nearly 10-12 shoots were formed. Regenerated shoots were individually isolated and rooted on a separate root inducing medium which consisted of MS medium supplemented with varying concentrations of IBA (4.9µM, 9.8µM, 19.6µM). Best rooting was, howver, achieved on 9.8µM IBA. Rooting initiated at the base of the shoot after 30 days and well developed roots were formed after 40-45 days of inoculation . The plantlets with elongated root and shoot systems were subjected to hardening and attempts are underway to establish these plantlets in the soil. Synthetic seeds were produced in Withania by encapsulating shoot apices using different concentrations (2%, 2.5% and 3%) of sodium alginate followed by their dropping in 75 mM calcium chloride. 2.5% sodium alginate turned out to be best composition for gel complexation and was prepared by dissolving either in distilled water or in MS medium devoid of agar. The seeds so formed were stored in refrigerator at 4oC and their viability was checked after 10, 20, 30, 40 and 50 days of storage. There was gradual reduction in the conversion rates and plantlet regeneration upon storage and the seeds prepared using sodium alginate dissolved in water were viable for a longer period than those prepared using sodium alginate dissolved in MS medium.
Master of Science-Biotechnology
Keywords: Micropropagation; Enhanced axillary branching, Synthetic seed production; Withania